THE PROPER WAGE FOR WORKERS DURING THE COVID-19 PANDEMIC ACCORDING TO THE GOVERNMENT REGULATION PERPECTIVE NUMBER 78 OF 2015 CONCERNING WAGES - Zanuar Bayu Pamungkas; Cholifatu Rohmah; Aris Prio; Umi Hanifah; Agus Suyatno (International Journal of Law and Legal Ethics, 2021)
Wages are an absolute that couldn’t be avoided. Wages are the companies’ obligation to their workers for their reciprocal efforts for the sake of the companies. However, during the covid-19 pandemic, there are obstacles to this wage, such as wage’s cut, suspension of THR, until housing of workers or layoffs. This study is intended to determine the implementation of government regulation number 78 of 2015 about wages for workers. This study uses empirical juridical based on online forms distributed via Google form. From this study the authors found several things that considered the case, there are delays, wage deductions and THR. In this problem, the average of it is caused by less income from consumers. Therefore, the government issued Government regulation number 78 of 2015 about Wages and Circular letter (SE) Number M/6/HK.04/IV/2021 About the Implementation of Provision of Religious Holiday Allowances in 2021 for workers/ laborers in companies. Whether the companies do not enforce the applicable regulations, it will be considered as a crime. According of legislation, the government had carried out the legal accountability to workers or laborers.